Antibody levels to multiple malaria vaccine candidate antigens in relation to clinical malaria episodes in children in the Kasena-Nankana district of Northern Ghana - Dodoo, Daniel (BioMed Central, 2011)
BACKGROUND: Considering the natural history of malaria of continued susceptibility to infection and episodes of illness that decline in frequency and severity over time, studies which attempt to relate immune response to protection must be longitudinal and have clearly specified definitions of immune status. Putative vaccines are expected to protect against infection, mild or severe disease or reduce transmission, but so far it has not been easy to clearly establish what constitutes protective immunity or how this develops naturally, especially among the affected target groups. The present study was done in under six year old children to identify malaria antigens which induce antibodies that correlate with protection from Plasmodium falciparum malaria. METHODS: In this longitudinal study, the multiplex assay was used to measure IgG antibody levels to 10 malaria antigens (GLURP R0, GLURP R2, MSP3 FVO, AMA1 FVO, AMA1 LR32, AMA1 3D7, MSP1 3D7, MSP1 FVO, LSA-1and EBA175RII) in 325 children aged 1 to 6 years in the Kassena Nankana district of northern Ghana. The antigen specific antibody levels were then related to the risk of clinical malaria over the ensuing year using a negative binomial regression model. RESULTS: IgG levels generally increased with age. The risk of clinical malaria decreased with increasing antibody levels. Except for FMPOII-LSA, (p = 0.05), higher IgG levels were associated with reduced risk of clinical malaria (defined as axillary temperature ≥37.5°C and parasitaemia of ≥5000 parasites/ul blood) in a univariate analysis, upon correcting for the confounding effect of age. However, in a combined multiple regression analysis, only IgG levels to MSP1-3D7 (Incidence rate ratio = 0.84, [95% C.I.= 0.73, 0.97, P = 0.02]) and AMA1 3D7 (IRR = 0.84 [95% C.I.= 0.74, 0.96, P = 0.01]) were associated with a reduced risk of clinical malaria over one year of morbidity surveillance. CONCLUSION: The data from this study support the view that a multivalent vaccine involving different antigens is most likely to be more effective than a monovalent one. Functional assays, like the parasite growth inhibition assay will be necessary to confirm if these associations reflect functional roles of antibodies to MSP1-3D7 and AMA1-3D7 in this population.